Порівняльна характеристика гендерних особливостей управлінської діяльності жінки та чоловіка = Comparative characteristics of gender-sensitive management of women and men - Jovyk, Tetyana; Maslova, Yuliya; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Jovyk Tetyana, Maslova Yuliya, Zukow Walery. Порівняльна характеристика гендерних особливостей управлінської діяльності жінки та чоловіка = Comparative characteristics of gender-sensitive management of women and men. Journal of Education, Health and Sport. 2016;6(6):11-22. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53957 http://ojs.ukw.edu.pl/index.php/johs/article/view/3543 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. Порівняльна характеристика гендерних особливостей управлінської діяльності жінки та чоловіка Comparative characteristics of gender-sensitive management of women and men Йовик Тетяна Олександрівна Jovyk Tetyana Oleksandrivna Національний університет «Острозька академія» National University „Ostrog Academy” Маслова Юлія Петрівна Maslova Yuliya Petrivna Національний університет «Острозька академія» National University „Ostrog Academy” Zukow Walery Zukow Walery UMK w Toruniu UMK in Torun У статті розглянуто та проаналізовано гендерні особливості управлінської діяльності жінки та чоловіка, подано порівняльну характеристику цих особливостей. Ключові слова: гендер, гендерний менеджмент, стать, управлінська діяльність. In the article considered the features of gender management of women and men and provided comparative description of these features. Key words: gender, gender management, gender, management activity.